2009
DOI: 10.1016/j.neulet.2008.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of midazolam on acquisition and extinction of conditioned taste aversion memory in rats

Abstract: Some intravenous anesthetic agents such as midazolam are known to induce anterograde and retrograde amnesia. We analysed the effect of midazolam by the conditioned taste aversion (CTA) acquisition and retention. After the rats were offered 0.1% sodium saccharin (Sac) as conditioned stimulus (CS), an intraperitoneal (i.p.) injection of several concentrations (5 ~ 30 mg/kg) of midazolam was followed by an i.p. injection of 0.15 M LiCl (2% of body weight) as unconditioned stimulus (US). The rats, which acquired C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Pre-conditioning control values of standard DW intake (SDW) are the mean of DW intake for the final 3 days of the water-restriction training period. Total Sac intake (%) on conditioning (C1-C3) and extinction (E1-E7) days were calculated as percentages against SDW, because saccharin intake on C1 is highly influenced by degree of neophobia to CS as a novel taste [16,20]. Because E1 was the day after the final conditioning day (C3), we used Sac intake on E1 as the parameter for acquisition of CTA memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-conditioning control values of standard DW intake (SDW) are the mean of DW intake for the final 3 days of the water-restriction training period. Total Sac intake (%) on conditioning (C1-C3) and extinction (E1-E7) days were calculated as percentages against SDW, because saccharin intake on C1 is highly influenced by degree of neophobia to CS as a novel taste [16,20]. Because E1 was the day after the final conditioning day (C3), we used Sac intake on E1 as the parameter for acquisition of CTA memory.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the acquisition and retention processes of memory has been demonstrated by a number of reports using the local blockade of N-methyl-D-aspartate receptor [6,7], protein synthesis of b-adrenergic receptor [13,14] in brain regions related to CTA memory or the extinction memory, the intraperitoneal injection of anesthetics, such as propofol or the a2-adrenergic blocker, yohimbine, [15,16] or a point mutation strategy in mice [17].…”
Section: Introductionmentioning
confidence: 99%
“…17 As was observed in humans, 18 midazolam caused temporary deficits in the acquisition of new memories (anterograde amnesia) in rodents. 19…”
mentioning
confidence: 99%
“…17 As was observed in humans, 18 midazolam caused temporary deficits in the acquisition of new memories (anterograde amnesia) in rodents. 19 The possible effects of the ketamine/midazolam combination on cognition may have not only clinical, but also research implications related to the welfare and normal behaviour of the animals. A deviation in behaviour caused by the anaesthesia could alter the outcome of research projects, especially in the neuroscience area.…”
mentioning
confidence: 99%
“…Adrenergic receptor antagonists are found to induce activity of noradrenergic neurons by blocking autoreceptors [ 38 ]. Recent studies also showed that an α 2-adrenergic blocker, yohimbine (1 mg/kg) suppressed the CTA acquisition and retention in rats [ 39 ]. In another study, an alpha-2 adrenoreceptor antagonist, methoxy-idazoxan (RX821002), was found to enhance the extinction of CTA in rats by enhancing arousal, alertness, awareness, or attention [ 36 ].…”
Section: Discussionmentioning
confidence: 99%